Validity and reliability of Kessler Psychological Distress Scale for Brazilian elderly: a cross-sectional study - Gabriella Oliveira de Albuquerque Lins; Nathália Angel da Silva Lima; Girliani Silva de Sousa; Fernanda Jorge Guimarães; Iracema da Silva Frazão; Jaqueline Galdino Albuquerque Perrelli
ABSTRACT Objective: to verify the validity and reliability of the Psychological Distress Scale for screening mental distress. Methods: a cross-sectional study with 75 elderly people. Psychological Distress scale and Self Reporting Questionnaire were used. Criterion validity was verified using Spearman's correlation and diagnostic accuracy measures. Cronbach's alpha coefficient was used to investigate reliability. Results: the total internal consistency of the Psychological Distress Scale was α=0.844. Concurrent validity between this instrument and the Self Reporting Questionnaire was ρ=0.722 (p<0.001). The best cut-off point for screening mental distress among elderly people was a total score greater than 14, with sensitivity equal to 75.47% and specificity equal to 85.0%. Conclusions: the scale was robust for screening mental distress, given its high reliability, in terms of homogeneity, and adequate criterion validity, whose best cut-off point for screening was a score greater than 14.